2020
DOI: 10.1007/s00265-020-02883-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in incubation behaviour and niche separation of two competing flycatcher species

Abstract: Food availability sets the stage for incubation behaviour of a female bird and thereby indirectly determines the nest temperature, which in turn affects development and metabolism of avian embryos. Changes in development and metabolism in turn are known to influence offspring's ability to adjust to environmental changes later in life. However, few studies have investigated the role of interspecific differences in incubation behaviour in relation to niche separation between competing sibling species. We studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…We can therefore only speculate about the specific underlying mechanism. Incubation behaviour (Koski et al 2020), thyroid hormones (Hsu et al 2019) and yolk androgens (Rice et al 2013) are all important early-life maternal effects that have previously been shown to have long-lasting effects on offspring performance in studies of collared flycatchers. We therefore consider these maternal effects as likely candidate drivers to the observed early-life (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We can therefore only speculate about the specific underlying mechanism. Incubation behaviour (Koski et al 2020), thyroid hormones (Hsu et al 2019) and yolk androgens (Rice et al 2013) are all important early-life maternal effects that have previously been shown to have long-lasting effects on offspring performance in studies of collared flycatchers. We therefore consider these maternal effects as likely candidate drivers to the observed early-life (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Collared flycatchers on Gotland usually lay one clutch per year, consisting of six eggs on average (range 4-8 eggs) that hatch in the beginning of June. Females lay one egg per day and the incubation is expected to start at the day when the female has laid her final egg (Koski et al 2020). The first eggs are laid in the first half of May and incubation is undertaken solely by females.…”
Section: Study Areamentioning
confidence: 99%
“…Perlut et al ., 2016) and/or prompting competition for resources leading to reduced nest attendance (e.g. Koski et al ., 2020) and parental condition (e.g. Ardia & Clotfelter, 2007).…”
Section: Introductionmentioning
confidence: 99%